Antifungal Potential of Propolis Extract Against Candida Albicans: Literature Review - Olivia Maheswari Soerjanto; Pepy Dwi Endraswari; Abdul Khairul Rizki Purba (GoAcademica Research & Publishing, 2023)
The increasing rate of Candida resistance against pharmacological drugs has become a particular focus in the medical world, especially considering the high mortality rate due to systemic infections caused by Candida. It is evident that the urgency of developing alternative medicines applies for potential natural ingredients like propolis. This literature review aims to discuss the antifungal effectiveness of propolis against C. albicans which is described by the MIC (minimum inhibitory concentration) and MFC (minimum fungicidal concentration) values from the test results. The search for relevant literature was conducted using the Google Scholar, ScienceDirect, and PubMed databases using the keywords